Apex scavenger movements call for transboundary conservation policies - Lambertucci, Sergio Agustin (2014)
Current changes in the environment and increases in threats to wildlife have prompted the need for a better understanding of species´ conservation requirements. Strategies for the conservation of large-sized animal species with large home ranges have included the creation of large protected areas, or for migrants, the creation of protected breeding, stop-over and wintering areas. We aim to describe the movement behaviour of Andean condors (Vultur gryphus), and to relate this movement to its significance in the conservation of this species and its environment. We examine whether current conservation strategies are sufficient to ensure the daily requirements of the species, and evaluate the degree to which breeding and foraging areas are covered by protected areas. We present as a new challenge the conservation of large-sized species that perform daily long-range movements across a number of political and ecological borders. Andean condors tagged with GPS-satellite transmitters make long daily flights from their breeding areas (mountains in Argentina and Chile) to their feeding areas (the steppe in Argentina) crossing over the Andean Cordillera. These flights demonstrate that current conservation strategies are insufficient to protect species with such daily movement patterns, and that new approaches are needed. Thus, it is necessary to gain a more in-depth knowledge of the movement ecology of these organisms through individual-level approaches integrating intrinsic (reproductive and foraging behaviour) and extrinsic (political and geomorphological boundaries) factors that shape movement patterns. Conservation efforts must include international cooperation aiming to combine the conservation of flagship species, the management of public and private lands, and the maintenance of valuable ecosystem services.